Metabolic engineering of Priestia megaterium for 2’-fucosyllactose production - Bu-Soo Park; Jihee Yoon; Jun-Min Lee; Sang-Hyeok Cho; Yoojeong Choi; Byung-Kwan Cho; Min-Kyu Oh (Microbial Cell Factories)
Abstract Background 2′-Fucosyllactose (2′-FL) is a predominant human milk oligosaccharide that significantly enhances infant nutrition and immune health. This study addresses the need for a safe and economical production of 2’-FL by employing Generally Recognized As Safe (GRAS) microbial strain, Priestia megaterium ATCC 14581. This strain was chosen for its robust growth and established safety profile and attributing suitable for industrial-scale production. Results The engineering targets included the deletion of the lacZ gene to prevent lactose metabolism interference, introduction of α-1,2-fucosyltransferase derived from the non-pathogenic strain, and optimization of the GDP-L-fucose biosynthesis pathway through the overexpression of manA and manC. These changes, coupled with improvements in lactose uptake and utilization through random mutagenesis, led to a high 2’-FL yield of 28.6 g/L in fed-batch fermentation, highlighting the potential of our metabolic engineering strategies on P. megaterium. Conclusions The GRAS strain P. megaterium ATCC 14581 was successfully engineered to overproduce 2’-FL, a valuable human milk oligosaccharide, through a series of genetic modifications and metabolic pathway optimizations. This work underscores the feasibility of using GRAS strains for the production of oligosaccharides, paving the way for safer and more efficient methods in biotechnological applications. Future studies could explore additional genetic modifications and optimization of fermentation conditions of the strain to further enhance 2’-FL yield and scalability.